The prevalence of celiac disease in patients with irritable bowel syndrome and its subtypes - Domżał-Magrowska, Danuta; Kowalski, Marek K.; Szcześniak, Piotr; Bulska, Magdalena; Orszulak-Michalak, Daria; Małecka-Panas, Ewa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Irritable bowel syndrome (IBS) and celiac disease (CD) share some gastrointestinal symptoms. Celiac disease should be considered in a differential diagnosis of IBS. Aim : To estimate the prevalence of predispositions to CD in patients with IBS and its subtypes. Material and methods : The study included 48 patients (40 women, 8 men; average age: 41.1 ±14.6 years) with IBS, and a control group: 20 healthy volunteers. All participants completed a questionnaire on their current gastrointestinal symptoms and had a blood sample taken to determine the HLA DQ2/DQ8 antigens and serum concentration of anti-tTG IgA and anti-DGP IgA and IgG. Results : The presence of HLA DQ2 or DQ8 was found in 50% of patients (n = 24) with IBS. In the control group the presence of HLA DQ2 was found in 4 (20%) patients and nobody had HLA DQ8. Increased levels of anti-tTG IgA were found in 5 (10.42%) patients with IBS, anti-DGP in 4 (8.33%), and anti-DGP IgG in 3 (6.25%). In the control group positive test result for anti-tTG was found in 2 (10%) patients; nobody had elevated anti-DGP IgA or IgG. A concomitant positive result of genetic testing and any elevated serum antibodies specific to CD was found in 12.5% of IBS patients (n = 6) and in none of the control group. Conclusions : Patients with IBS, regardless of the subtype, significantly more often than healthy controls have the predisposing genetic factors (HLA DQ2/DQ8) underlying the development of CD.